A model system to explore the detection limits of antibody-based immuno-SPECT imaging of exclusively intranuclear epitopes - Veal, M; Dias, G; Kersemans, V; Sneddon, D; Faulkner, S; Cornelissen, B (Society of Nuclear Medicine, 2021)
PURPOSE: Imaging of intranuclear epitopes using antibodies tagged to cell penetrating peptides (CPPs) has great potential given its versatility, specificity and sensitivity. However, this process is technically challenging because of the location of the target. Previous research has demonstrated a variety of intranuclear epitopes that can be targeted with antibody-based radioimmunoconjugates (RICs). Here, we developed a controlled expression model of nuclear localised GFP to interrogate the technical limitations of intranuclear SPECT using RICs, notably the lower target abundance detection threshold. METHODS: We stably transfected the lung adenocarcinoma cell line H1299 with an EGFP-tagged histone (H2B-EGFP) and generated four cell lines expressing increasing levels of GFP (EGFP). EGFP levels were quantified using western blot, flow cytometry, and ELISA. An anti-GFP antibody (GFP-G1) was modified using DBCO-N3 based strain-promoted azide-alkyne cycloaddition (SPAAC) with the CPP TAT (GRKKRRQRRRPPQGYG-hA(N3)), which also includes a nuclear localisation sequence, and the metal ion chelator N3-Bn-DTPA to allow radiolabelling with 111In. Cell uptake of [111In]In-GFP-G1-TAT was evaluated across five cell clones expressing different levels of H2B-EGFP in vitro. Tumour uptake in xenograft-bearing mice was quantified to determine the smallest amount of target epitope that could be detected using [111In]In-GFP-G1-TAT. RESULTS: We generated four H1299 cell clones expressing different levels of H2B-EGFP (0 - 1 Mcopies/cell). GFP-G1 monoclonal antibody was produced and purified in house and selective binding to H2B-EGFP was confirmed. The affinity (KD) of GFP-G1 was determined as 9.1 ± 3.0 nM. GFP-G1 was conjugated to TAT and DTPA. [111In]In-GFP-G1-TAT uptake in H2B-EGFP expressing cell clones correlated linearly with H2B-EGFP expression (P < 0.001). In vivo xenograft studies demonstrated that [111In]In-GFP-G1-TAT uptake in tumour tissue correlated linearly with expression of H2B-EGFP (P = 0.004) and suggested a lower target abundance detection threshold of approximately 240,000 copies per cell. CONCLUSION: Here, we present a proof of concept demonstration that antibody-based imaging of intranuclear targets is capable of both detecting the presence of an epitope of interest with a copy number above 240,000 copies per cell and is capable of determining differences in expression level above this threshold